CULTURAL ANALYSIS OF ELTON JOHN’S SONG SATURDAY NIGHT’S ALRIGHT FOR FIGHTING - Dwi Ainur Riza; Wiwin Anggraeni Kurniawati; Anggoro Cahyo Wicaksono; Achmad Maulana Marharendra; Rindrah Kartiningsih; Rommel Utungga Pasopati (LPPM Universitas PGRI Adi Buana, 2025)
This study analyzes Elton John's song Saturday Night's Alright for Fighting, co-written with lyricist Bernie Taupin, through a cultural studies perspective. Released in 1973, the song is known for its energetic rock style and lyrics depicting teenage nightlife, drinking, and fighting. More than just a work of entertainment, the song can be seen as a cultural text depicting the practices and identities of working-class youth in Britain in the 1970s. Drawing on Stuart Hall's theories of representation and encoding/decoding, this study examines how meanings of freedom, aggression, and social identity are constructed in the lyrics and how listeners interpret these meanings based on their cultural and class positions. Furthermore, Dick Hebdige's subcultural theory is used to understand how music and style function as symbolic practices and forms of resistance within working-class culture. Recent research on youth and popular music suggests that cultural practices, including music, often serve as crucial spaces for the negotiation of identity and masculinity, particularly for marginalized young working-class men. In conclusion, this article argues that Saturday Night's Alright for Fighting not only depicts the spirit and rebellion of youth but also reflects the struggles, hopes, and cultural styles of working-class masculinity.